ANALISIS KELAYAKAN USAHA DAN STRATEGI PEMGEMBANGAN USAHA TANI JAMUR TIRAM PUTIH PADA UD SRIKANDI - Melynia Febi Hardi; Rulan L. Manduapessy (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to evaluate the business feasibility and development strategy of white oyster mushroom farming at UD Srikandi. In the research results, the financial, marketing and technical/technological aspects were declared feasible, while the legal and management aspects were declared not yet feasible. For the business development strategy, a SWOT analysis was carried out to identify internal and external factors that influence UD Srikandi. Alternative strategies are then determined by focusing on SO strategies or supporting aggressive strategies, namely maintaining and improving partnerships with customers, developing the use of technology, and maintaining product quality. In this way, UD Srikandi can maintain business viability and develop the white oyster mushroom farming business well